THE IMPACT OF THE MANAGER’S LEADERSHIP STYLE ON THE ADAPTATION PROCESS OF EMPLOYEES : Case study of the DIAS-System - Mäkkylä, Mona (My University, 2020)
Currently the digitalizing world and rapid development cause constant need for changes in organisations. The changes in organisations may occur due to organisational changes, such as mergers & acquisitions or due to technological innovations, such as new digital products for helping the organisations to improve the performance. The constant need for implementing changes in organisations forces management to consider, how employ-ee’s individual adaptation process could be enhanced by their managers. The purpose of this thesis is to provide solutions on how manager’s leadership style may enhance the adaptation process of an individual employee throughout change activities. The theoretical framework discusses the various change constructs and introduces leadership styles based on their categorization. In addition, comparisons of organisation models are introduced. A conceptual framework was formed based on the theoretical background of the study. The empirical study was conducted as a qualitative study by using a case study method. The case study is formed around a new digital platform for real estate sales transactions, the DIAS system. The case study was conducted by using themed semi-structed interviews, in the early spring of 2020. The data of the thesis was collected by interviewing five different leaders in organisations that have integrated the DIAS-system into their organisation core practices. The findings of the study present a thorough viewpoint of the current state of inte-gration of the DIAS system in the participant organisations. Based on the interview find-ings the full integration of a new processes requires top management decision to use resources on the personal guidance as well as support individual adaptation by setting standards for change adaptation rewarding. Based on this study, the managers integrating change procedures shall emphasize clear communication and positive atmosphere while presenting the cases. Wide under-standing of diverse readiness to change settings of the employees is also desired. For future research, the employee perspective on the leadership style impact may add value to the current management and organisational change research by including the individual employee perspective.

Tällä hetkellä digitalisoituva maailma ja nopea kehitys aiheuttaa jatkuvaa muutoksen tarvetta organisaatioissa. Muutokset saattavat tapahtua organisaatiomuutoksien, esimerkiksi fuusioiden tai yrityskaupan tai teknologisten innovaatioiden, kuten uusien digitaalisten prosessien vuoksi. Jatkuva muutoksien toteuttamisen tarve organisaatioissa pakottaa johdon harkitsemaan, miten työntekijän yksilöllistä omaksumisprosessia voidaan edistää johdon toimesta. Tämän tutkimuksen tarkoitus on tuottaa ratkaisuja siihen, kuinka johtajan oma johtamistyyli voi edistää yksittäisen työntekijän omaa omaksumista muutosprosessien läpi. Tutkimuksen teoreettinen viitekehys tarkastelee useita muutoskäsitteitä ja esittelee johtamismalleja niiden kategorisoinnin perusteella. Synteesi on muodostettu teoreettiseen viitekehykseen perustuen. Empiirinen osa tutkimuksesta toteutettiin laadullisena tutkimuksena käyttäen yksittäistä tapaustutkimusta. Tapaustutkimus perustuu uuden digitaalisen asuntokauppajärjestelmän, DIAS-järjestelmän käyttöönottoon eri organisaatioissa. Tutkimus toteutettiin tekemällä puoliksi strukturoituja teemahaastatteluja alkukeväällä 2020. Tutkimuksen aineisto kerättiin haastattelemalla viittä eri johtajaa tai tiiminvetäjää organisaatioissa, jotka ovat ottaneet DIAS-järjestelmän käyttöönsä heidän ydintoimissaan. Tutkimuksen tulokset esittävät perusteellisen näkökulman DIAS-järjestelmän integraation nykytilasta tutkimukseen osallistuneissa organisaatioissa. Haastattelujen perusteella uusien prosessien täysi integraatio vaatii johdolta päätöksiä käyttää resursseja henkilökohtaiseen ohjaukseen ja yksilöllisen omaksumisen tukemiseen asettamalla arvosteluperusteita muutoksen omaksumisen palkitsemiseksi. Tutkimuksen perusteella johtajien tulisi korostaa selkeää viestintää ja positiivista ilmapiiriä muutosprosessien esittelytilanteissa. Laaja ymmärrys työntekijöiden moninaisista puitteista muutosvalmiudelle on myös tutkimuksen perusteella suotavaa. Tulevaisuudessa työntekijän perspektiivistä johtamismallien vaikutuksen tutkiminen toisi lisäarvoa johtamisen ja organisaatioiden muutosten johtamisen tutkimukseen.
Keywords: Change management, leadership styles, individual adaptation